Budgetary decomposition and yield spreads. Issue 15 (12th October 2016) - Afonso, António; Jalles, João Tovar
ABSTRACT: With a panel VAR of 10 Euro area countries, we studied the budgetary determinants of government bond yield spreads vis-à-vis Germany between 1999Q1 and 2012Q4. We find that rising bid ask, VIX and debt differentials increase yield spreads; and improvements in the budget balance, higher growth prospects and depreciation lower the spreads. Moreover, rises in public wages or in social expenditure increase spreads, while increases in direct and indirect taxes lower the yield spreads. In the post-2007Q3 crisis period, rising expenditure components (except subsidies) increased spreads.